2006
DOI: 10.1002/cne.20944
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Prox1 during mouse cochlear development

Abstract: We carried out an analysis of the expression of Prox1, a homeo-domain transcription factor, during mouse inner ear development with particular emphasis on the auditory system. Prox1 is expressed in the otocyst beginning at embryonic day (E)11, in the developing vestibular sensory patches. Expression is down regulated in maturing (myosin VIIA immunoreactive) vestibular hair cells and subsequently in the underlying support cell layer by E16.5. In the auditory sensory epithelium, Prox1 is initially expressed at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
148
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(164 citation statements)
references
References 60 publications
(66 reference statements)
12
148
0
1
Order By: Relevance
“…No immunoreactivity for ATOH1, LHX3 or MYO6 is detected at this age in the auditory epithelium ( Figure 1, N-P). This contrasts with previous descriptions of ATOH1 expression detected by in situ hybridization at E13 within the auditory region, or as revealed in transgenic mice expressing beta-galactosidase or green fluorescent protein under control of the ATOH1 promoter in the basal turn of the cochlea at E14.5 (Bermingham et al, 1999;Bermingham-McDonogh et al, 2006;Lumpkin et al, 2003;Woods et al, 2004). There is also one description of immunologic detection of ATOH1 in the basal cochlea at E14.5 (Chen et al, 2002).…”
Section: Late Labyrinth-e15-16mentioning
confidence: 62%
See 1 more Smart Citation
“…No immunoreactivity for ATOH1, LHX3 or MYO6 is detected at this age in the auditory epithelium ( Figure 1, N-P). This contrasts with previous descriptions of ATOH1 expression detected by in situ hybridization at E13 within the auditory region, or as revealed in transgenic mice expressing beta-galactosidase or green fluorescent protein under control of the ATOH1 promoter in the basal turn of the cochlea at E14.5 (Bermingham et al, 1999;Bermingham-McDonogh et al, 2006;Lumpkin et al, 2003;Woods et al, 2004). There is also one description of immunologic detection of ATOH1 in the basal cochlea at E14.5 (Chen et al, 2002).…”
Section: Late Labyrinth-e15-16mentioning
confidence: 62%
“…These transcription factors fall into three general families: SOX (a subset of HMG box), basic helix-loop-helix (bHLH) and LHX (LIM homeodomain), respectively. Limited information has been reported regarding the expression of these genes during inner ear development (Bermingham et al, 1999;Bermingham-McDonogh et al, 2006;Chen et al, 2002;Kiernan et al, 2005;Lumpkin et al, 2003;Sage et al, 2005;Woods et al, 2004). We focused on the time interval between initial hair cell differentiation and the adult.…”
Section: Resultsmentioning
confidence: 99%
“…Prox1 is an early marker of the developing pillar and Deiters' cells (Bermingham-McDonogh et al, 2006). When we compared the Prox1 labeling in whole mounts of cochlea from wild type and Fgfr3 Ϫ/Ϫ mice, we found that cochlea from the Fgfr3 Ϫ/Ϫ mice have a very different appearance.…”
Section: Resultsmentioning
confidence: 93%
“…1D,G). At this time, Fgfr3 is expressed at the base of the cochlea in the region of the developing sensory epithelium that contains the Prox1-expressing cells (Bermingham-McDonogh et al, 2006). The expression of Fgfr3 proceeds rapidly to the apex, and by E18.5, Fgfr3 is expressed throughout the length of the cochlea (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Prox1 homologues have been identified in other vertebrates, including Xenopus, zebrafish, chicken, and human (Tomarev et al, 1996;Glasgow and Tomarev, 1998;Ny et al, 2005). In vertebrates, Prox1 is expressed in the developing neural retina, lens, cochlea, spinal cord, brain, skeletal muscle, heart, liver, pancreas, and in the endothelial cells that will give rise to the lymphatic vasculature (Oliver et al, 1993;Tomarev et al, 1996;Glasgow and Tomarev, 1998;Burke and Oliver, 2002;Wigle et al, 2002;Wang et al, 2005;Bermingham-McDonogh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%